2011
DOI: 10.1002/jccs.201190107
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition of Gold Nanoparticles on Pencil Graphite by Fast Scan Cyclic Voltammetry

Abstract: Gold nanoparticles (AuNPs) were electrodeposited on the surface of pencil graphite (PG) by fast scan cyclic voltammetry without using any additives in acidic medium. The effect of deposition time on the size of electrodeposited AuNPs was investigated in sulfuric acid as a supporting electrolyte. The deposition time was varied by varying the scan rate, number of cycles and applied potential range. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD) were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
(49 reference statements)
3
22
0
Order By: Relevance
“…KCl)) favor the creation of new nucleation sites over the growth of previously created nuclei. [26][27][28][29] Figures 2(a-d) demonstrate the effect of Vapp on the AuNPs electrodeposited on MoS2/SPGE, when varying the Vapp potential from +0.1 to -0.2 V. It is observed that the application of decreasing Vapp potentials, leads gradually to a larger number of nucleation sites and hence to larger density of smaller, evenly distributed AuNPs, corroborating earlier work. [27][28] Two growth modes are evident, depending on the Vapp potential.…”
Section: Electrochemical Deposition Of Gold Nanoparticles On Mos2 Nansupporting
confidence: 83%
See 1 more Smart Citation
“…KCl)) favor the creation of new nucleation sites over the growth of previously created nuclei. [26][27][28][29] Figures 2(a-d) demonstrate the effect of Vapp on the AuNPs electrodeposited on MoS2/SPGE, when varying the Vapp potential from +0.1 to -0.2 V. It is observed that the application of decreasing Vapp potentials, leads gradually to a larger number of nucleation sites and hence to larger density of smaller, evenly distributed AuNPs, corroborating earlier work. [27][28] Two growth modes are evident, depending on the Vapp potential.…”
Section: Electrochemical Deposition Of Gold Nanoparticles On Mos2 Nansupporting
confidence: 83%
“…In this contribution, we show that these requirements can be met under well controlled electrochemical deposition (ECD) conditions. 15,[26][27][28][29][30][31] ECD is also free of critical drawbacks such as the formation of "free" AuNPs, which usually coexist with AuNPs@MoS2 hybrids in solution-based routes. 11,22,24,[32][33] nanosheets (MoS2 NSs) on commercial screen-printed gold electrodes (SPGEs) (1); decoration of MoS2 NSs with AuNPs (to create AuNPs@MoS2 NSs) following an optimized chronoamperometric (CA) route (2); assembly of ssDNA capture probe: anti-miRNA-21 (CP), miRNA-21 target (TR) and signal amplification probe (AP) on AuNPs@MoS2/SPGE sensor (3)(4)(5); chronocoulometric (CC) detection of miRNA (TR) by monitoring [Ru(NH3)6] 3+ (RuHex) electrostatically bound to phosphate backbones of oligonucleotides (6).…”
Section: ▪ Introductionmentioning
confidence: 99%
“…To remove the adsorbed species that have been generated from the first set of scan cycles, the electrodes were taken out from the solution and thoroughly rinsed with distilled water between the two sets. 34,35 For the purpose of deposition, the three-electrode system (Pt wire as counter and Ag/AgCl as refer- 6).…”
Section: Resultsmentioning
confidence: 99%
“…Nanomaterials may be immobilized or prepared on GE surfaces via various techniques, including chemical vapor deposition [11], electrochemical deposition from a metal precursor [12][13][14][15], or electro chemical deposition from polymer attached NPs [16,17]. Chemical vapor deposition and electrochemical deposition techniques are fast processes and, therefore, produce poorly reproducible results.…”
Section: Methods For Immobilizationmentioning
confidence: 99%